Peacebuilding Strategies in Nigeria’s Ethnic Space: Specific Focus on Conflict-Spot in Kaduna Communities - Lamidi, Kazeem Oyedele; Olaleye, Oluseyi Idowu; Taleat, Bisiriyu Abiodun (International Journal of Criminology and Sociology, 2022)
This paper contextualised the subject matter and its strategies by providing insights on the development, peace and conflict in the Nigerian environment; explicating the peace and conflict impact assessment; exposing the causal factors for communal conflict; and analysing the strategies across the main tribes in Nigeria with specific focus on Kaduna communities. It drew largely on secondary sources whose contents were explicitly analysed for this contextual discourse. It found out that there were internal mechanisms put in place towards engendering peace building across the major tribes in Nigeria. It enlisted obtainable peacebuilding strategies in Kaduna communities. It concluded that a remarkable feature of the peace building strategies is that it does not only aim at conflict resolution, but also ensures peaceful co-existence scenes and harmonious relationships between and among conflicting people or communities. However, the latter still remains challenging owing to a low human development index and civic orientations.